E-kolej: the relationship of user satisfaction and usage to individual performance / Rapeah Mohd Redzuan - Mohd Redzuan, Rapeah (2013)
eKolej has been utilized in Universiti Teknologi Mara (UiTM) since 2006 as the hostel management system. The implementation of the system was seen had improved hostel accommodation process rather than manual system that was used previously. There is no research being conducted to evaluate individual performance which reflected by the satisfaction of users and the usage of the system. Survey data from 112 respondents of eKolej system's user in 20 UiTM's campuses were used.The users include of Hostel Manager, Assistant Hostel Manager and Hostel Supervisor. From data analyses, it has revealed that the level of eKolej system usage had been affected by Assistant Hostel Manager and Hostel Supervisor who using the system more for operational tasks rather than managers who frequently use eKolej for reports view. User satisfaction and individual performance for each level position of staff that using eKolej system was identified as high with average mean more than3.5. Nevertheless, the main objective of this study is to identify the relationship between user satisfaction and usage to individual performance based on model adapted from Hou (2012). The data were analyzed by using Pearson Correlation and Multiple Regressions to identify the relationship. The results indicate the relationship of user satisfaction and system usage to individual performance is positive. On the other words, higher levels of EUCS or system usage would lead to improve individual performance. However, EUCS was determined has strong relationships and the best predictor of individual performance compared to system usage. Thus, by better understanding of the relationship, the indication for system improvement is determined.